Clinical Research Progress on Carcinogenesis of Different Pathological Types of Colorectal Polyps - YU Rong, DONG Weiguo, TIAN Shan, WANG Ting (Zhongguo quanke yixue, 2023)
Colorectal cancer (CRC) is one of the most common tumors in the world. Colorectal polyps are local protuberant lesions that elevate the intestinal mucosa, and about 90% of CRC is evolved from polyp. According to the traditional concept, the occurrence and development of CRC is mostly through the "adenoma-cancer" sequence. However, studies have found that serrated polyps also form subclasses with different morphology and genes, and are closely related to microsatellite unstable CRC. About 15%-30% of CRC develops through the "serrated polyp-cancer" pathway. This article mainly reviewed the clinical characteristics of colorectal adenoma, serrated polyp and post-inflammatory polyps, through retrospective analysis of large samples, to summarize the incidence of different pathological types of colorectal polyps in the progression of carcinogenesis and the follow-up monitoring after polypectomy, so as to provide a better reference for follow-up monitoring of polyp patients and early screening and treatment of precancerous lesions.